African developments: political trends in recent elections in Sub-Saharan Africa - Judith Vorrath (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Multiparty elections have become frequent events in almost all countries of sub-Saharan Africa (SSA). But in 2010 and 2011 an exceptionally high number of elections have been held. By mid-20111 presidential and/or parliamentary elections had taken place in 20 countries. While voting has become a regular occurrence in many of these countries, has it been accompanied by an improvement in democratic quality? An analysis of recent elections and trends since the last round of voting produces an ambiguous picture. On the positive side, the relative stability of democracies in several small island states, such as Mauritius, has been confirmed. There have also been encouraging signs in the competitiveness and fairness of elections in a few countries with hybrid regimes, such as Nigeria; others, such as Guinea and Côte d'Ivoire, have (re)introduced voting after ruptures. Yet these slight improvements have often been accompanied by violence. Furthermore, many regimes restrict political freedom and competition and use elections more as a façade for their continuing rule, as in the Central African Republic (CAR) and Rwanda. In fact, almost half of the 20 countries that have recently held elections are showing a worrying tendency to maintain or even step up authoritarian measures and political exclusion. Compared to the 1980s, democratic quality has generally improved in SSA, but change has slowed or not been consolidated in many countries. A wave of upheavals and revolutions as in the Arab world remains unlikely in SSA in the near future. The strategies and instruments applied by international actors therefore need to be adapted to the varying speeds and stages of democratization within the region. Where basic respect for the rules of the game and political freedoms have been established, electoral assistance remains a key tool. But where such authoritarian practices as the harassment of civil society or restrictions of the freedom of the press prevail, greater emphasis must be placed on the need for a level political playing field and meaningful institutional reforms. Economic and security considerations remain important for EU and US actors, but reluctance to pay more than lip service to the effective promotion of democratisation may be a serious miscalculation. All too often in the past, political repression and exclusion have sown the seeds for subsequent instability and conflict. As patterns in West Africa and Central/East Africa differ, external actors also need to adopt stronger regional approaches, and African regional organizations should play a growing role in regime transformation.
Keywords: 330